Understanding heat stress in beef cattle - Brown-Brandl, Tami M (Brazilian Journal of Animal Science, 2018)
Thermal stress is the result of a misbalance between heat produced or gained from the environment and the amount of heat lost to the environment. The level of thermal stress can range from minor or no effect to death of vulnerable animals. Under summertime conditions, thermal stress results in hyperthermia or heat stress. Heat stress in feedlot cattle is a common summertime occurrence in cattle-producing parts of the world (USA, Australia, Brazil, etc.). Effects on animals experiencing heat stress include decreases in feed intake, animal growth, and production efficiency. During these extreme events, animal losses can exceed 5% of all cattle on feed in a single feedlot. Luckily, these extreme events are generally very localized and last only a day or two. However, these losses can be devastating to individual producers within the affected area. The level of heat stress an individual animal will experience is a result of a combination of three distinct components: environmental conditions, individual animal susceptibility, and management of the herd. Environmental components include temperature, humidity, wind speed, and solar radiation. Several indices have been developed to summarize the different components into a single value. Individual animal susceptibility is influenced by many different factors including coat color, sex, temperament, previous health history, acclimation, and condition score. Finally, management greatly influences the effects of thermal stress. Management factors can be broken into four distinct categories: feed, water, environmental influences, and handling. Understanding these risk factors and how each one influences animal stress will aid in the development of management strategies and how to implement them. Management strategies that can be employed at the right time and to the correct groups of animals will increase benefits to the animals and limit costs for the producers
Keywords: animal responses; feedlot; heat waves; management